'NASPOT 12 O' and 'NASPOT 13 O' sweetpotato - Mwanga, Robert O.M.; Kyalo, Gerald; Ssemakula, G.N.; Niringiye, C.; Yada, B.; Otema, M.A.; Namakula, J.; Alajo, A.; Kigozi, B.; Makumbi, R.N.N.; Ball, Anna-Marie; Grüneberg, W.J.; et al. (American Society for Horticultural Science, 2016)
Two sweetpotato [Ipomoea batatas L. (Lam.)] cultivars, NASPOT 12 O (Namulonge sweetpotato 12 orange-fleshed) and NASPOT 13 O (Namulonge sweetpotato 13 orange-fleshed) were approved for release by the Ugandan Plant Variety Release Committee (UPVRC) in Nov. 2013 (Ssemakula et al., 2013). This brings to 22, the number of sweetpotato cultivars officially released between 1999 and 2013 by the National Sweetpotato Program in Uganda (Mwanga et al., 2011; Ssemakula et al., 2013). The two cultivars herein described and released in 2013, have high average storage root yields, 43.1 t·ha−1 ('NASPOT 12 O') and 27.8 t·ha−1 ('NASPOT 13 O') on station, and 14.9 t·ha−1 ('NASPOT 12 O') and 9.7 t·ha−1 ('NASPOT 13 O') on farm compared with the national on-farm average for Uganda of 4.5 t·ha−1 (FAOSTAT 2010; Low et al., 2009). The cultivars have acceptable root shape, high dry matter content (DMC) (>30%) with good-to-excellent consumer qualities. The cultivars also have moderate levels of field resistance to sweetpotato virus disease (SPVD) and alternaria bataticola blight. The two cultivars were bred targeting development of vitamin A–rich (biofortified) orange-fleshed sweetpotato (OFSP). OFSP have been shown to be both effective for increasing maternal and child vitamin A intake and status (Hotz et al., 2012; Ruel and Alderman, 2013). The potential of the two OFSP cultivars to contribute to food and nutrition security in Uganda and the developing world is high (Low et al., 2007; Ruel, 2001), especially where high dry matter and starchy sweetpotatoes are preferred. The cultivars can be used directly if adapted in similar agroecologies in sub-Saharan Africa and globally and/or used as parents in breeding programs to develop locally adapted cultivars that meet high dry matter consumer preferences.